2018
DOI: 10.3390/cancers10110437
|View full text |Cite
|
Sign up to set email alerts
|

CCND1 Splice Variant as A Novel Diagnostic and Predictive Biomarker for Thyroid Cancer

Abstract: Cyclin D1 protein is aberrantly overexpressed in thyroid cancers, but mutations of the CCND1 gene are rare in these tumors. We investigated the CCND1 rs9344 (G870A) polymorphism and the expression profiles of wild-type CCND1a and shortened oncogenic isoform CCND1b at the mRNA and protein levels in 286 thyroid tumors. Genotype AA of rs9344 was associated with high expression of CCND1b mRNA and was more frequently found in thyroid cancer than in benign tumors. The mRNA expression levels of CCND1b were higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Guo et al (51) observed that the lncRNA NR2F1-AS1 sponged miRNA-338-3p to upregulate CCND1 expression and promote thyroid carcinoma progression. In addition, Jeon et al (52) proposed that the CCND1 splice variant may serve as a biomarker for the diagnostic and prediction of thyroid carcinoma. These findings confirmed that the overexpression of CCND1 serves a key role in the promotion of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al (51) observed that the lncRNA NR2F1-AS1 sponged miRNA-338-3p to upregulate CCND1 expression and promote thyroid carcinoma progression. In addition, Jeon et al (52) proposed that the CCND1 splice variant may serve as a biomarker for the diagnostic and prediction of thyroid carcinoma. These findings confirmed that the overexpression of CCND1 serves a key role in the promotion of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A casuistic study can also not be done in association of cyclin D1 with gliomas (Aytekin et al, 2014). On the other hand, there are references of the association between polymorphism and thyroid and breast cancer ((Jeon et al, 2018;Thakur et al, 2018), however the scarce ones are studies in Brazilian population. Cyclin D1, encoded by the CCND1 gene, is an important regulatory protein of the G1 phase transition to a phase of the cell cycle and has a great impact on the control of cell proliferation and differentiation (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, only the rs603965 polymorphism could be analyzed because this was the only CCND1 polymorphism that was investigated by multiple different studies. Previous experimental studies found that the rs603965 polymorphism was located at the conjunction of exon 4 and intron 4 of CCND1 gene, the G to A variation in this locus was associated with a shorter transcription and a 55 amino acids loss of the C‐terminal domain of CCND1 (Jeon, Kim, Jeong, Bae, & Jung, ; Vodicka et al., ), which may greatly alter the activity of CCND1 and give rise to the development of brain tumor. Second, the etiologies of different types of brain tumor may be somewhat different.…”
Section: Discussionmentioning
confidence: 99%